Effect of solar radiation on the survival of the fungus Beauveria bassiana (Bals.) Vuill. in laboratory and field - VELEZ-A., PATRICIA EUGENIA; MONTOYA-R., ESTHER CECILIA (Revista Colombiana de Entomología, 1995)
In an attempt to evaluate in the laboratory the effect of different times of exposure to the UV light at the sunlight simulator on the germination of conidia ofBeauveria bassiana 191 650, oil and water suspensions of B. bassiana 191 650 were prepared. Germination tests carried out in Nutrient Gelatin showed protection of the standard mixture of oils to the conidia exposed 90 minutes to the simulator as compared to conidia in water suspension. No direct germination of conidia of B. bassiana 191 650 in oil and water suspensions, sprayed on coffee leaf discs and exposed 0 - 60 minutes to the simulator, was observed. However, B. bassiana 191 650 sprayed to coffee leaf discs in the standard mixture of oils showed viability after 60 minutes of exposure to the sunlight simulator, as evaluated by the unity forming colonies (UFC) in the nutrient medium. The spraying of different formulations of B. bassiana 9002 to coffee berries in Colombian coffee plantations showed defined trends in some treatments. It was observed that the longer the exposure time to the sunlight radiation, the less viability of the propagules of this fungus. The variables temperature and relative humidity were relatively constant during the field study. Consequently, the variable global radiation played an important role in the response of the treatments.